Draft Aphaenogaster genomes expand our view of ant genome size variation across climate gradients - Lau, Matthew K.; Ellison, Aaron M.; Nguyen, Andrew; Penick, Clint; DeMarco, Bernice; Gotelli, Nicholas J.; Sanders, Nathan J.; Dunn, Robert R.; Helms Cahan, Sara (PeerJ, 2019)
Given the abundance, broad distribution, and diversity of roles that ants play in many ecosystems, they are an ideal group to serve as ecosystem indicators of climatic change. At present, only a few whole-genome sequences of ants are available (19 of >16,000 species), mostly from tropical and sub-tropical species. To address this limited sampling, we sequenced genomes of temperate-latitude species from the genus Aphaenogaster, a genus with important seed dispersers. In total, we sampled seven colonies of six species: Aphaenogaster ashmeadi, Aphaenogaster floridana, Aphaenogaster fulva, Aphaenogaster miamiana, Aphaenogaster picea, and Aphaenogaster rudis. The geographic ranges of these species collectively span eastern North America from southern Florida to southern Canada, which encompasses a latitudinal gradient in which many climatic variables are changing rapidly. For the six genomes, we assembled an average of 271,039 contigs into 47,337 scaffolds. The Aphaenogaster genomes displayed high levels of completeness with 96.1% to 97.6% of Hymenoptera BUSCOs completely represented, relative to currently sequenced ant genomes which ranged from 88.2% to 98.5%. Additionally, the mean genome size was 370.5 Mb, ranging from 310.3 to 429.7, which is comparable to that of other sequenced ant genomes (212.8–396.0 Mb) and flow cytometry estimates (210.7–690.4 Mb). In an analysis of currently sequenced ant genomes and the new Aphaenogaster sequences, we found that after controlling for both spatial autocorrelation and phylogenetics ant genome size was marginally correlated with sample site climate similarity. Of all examined climate variables, minimum temperature, and annual precipitation had the strongest correlations with genome size, with ants from locations with colder minimum temperatures and higher levels of precipitation having larger genomes. These results suggest that climate extremes could be a selective force acting on ant genomes and point to the need for more extensive sequencing of ant genomes.
Keywords: Ants; Genomics; Ecology; Climate change; Evolution; Adaptation